Effectiveness of adhesive bonding in structural steel connections - Shafiq, N. (CI-Premier Pte Ltd, 2017)
This research study was focused to determine the effectiveness of adhesive joints in structural steel construction. Flexural testing and analysis of 36 structural steel plates jointed with three different overlapping length with different adhesive thickness showed the higher capability of its application in structural steel connections under flexural loads. Adhesive joints in structural steel connections for structures subjected to light to medium loads would become very effective alternatively in the applications where welding connections are required to be avoided. Adhesive joints may also avoid the chances of material embitterment at the joints under certain environmental conditions.